A Survey of Population Growth Versus Resources and Sustainability Debate - Pradhan, Baburam (Nepal Population Journal, 2026)
The main objective of this work is to investigate how the population growth and resources debate evolved and to identify the key players of this debate. The data source of the review article is available literature in the field. To make the review process scientific and reproducible, literature is selected by author-defined criteria, and the taxonomy of Cooper (1988) and theoretical saturation are used to define the sample size for the study. The data is analyzed by the Framework Analysis method. The population and resource debate began with Thomas Malthus when they published their first book, An Essay on the Principle of Population, in 1798, where they outlined how overpopulation could lead to famine. Malthus was mostly criticised in their time, but in the 20th century, they earned some ardent supporters labeled as neo-Malthusians who advocated for active measures of population control to avoid potential famine and to protect the environment. Dennis Meadows and their team provided a scientific basis for the neo-Malthusian proposition. Cornucopian Ester Boserup and Julien Simon opposed Malthusian and neo-Malthusian assumptions and proposed a population as a resource proposition. UN-promoted sustainable development is the recent agenda in this debate. This work has concluded that the debate of population growth versus resources is not settled yet, as the pressure of population on the environment continues. So, the balance between population growth and resource consumption is an area to investigate further.